Overview of Dysmenorrhea Incidence Among Intrauterine Device Users in the Working Area of Balowerti Community Health Center Kediri City - Satna Henti; Indah Rahmaningtyas; Finta Isti Kundarti; Eny Sendra (Gayaku Publisher, 2026)
Background: Dysmenorrhea is a potential side effect experienced by users of Intrauterine Devices (IUDs), particularly during the initial period of use, due to increased prostaglandin levels that trigger uterine contractions. This complaint can affect the user's comfort and potentially lead to the discontinuation of IUD use. This study aimed to describe the incidence of dysmenorrhea among IUD users in the working area of ​​the Balowerti Community Health Center (Puskesmas), Kediri City, based on pain intensity, characteristics, and duration. Methods: A descriptive study design was employed, involving a population of 40 women who had used an IUD for less than six months within the Balowerti Community Health Center's working area. A sample of 29 respondents was selected using purposive sampling. Data were collected through interviews using the Numeric Rating Scale (NRS) and analyzed using univariate analysis. Results: The majority of respondents experienced mild pain (65.5%), followed by moderate pain (27.6%) and severe pain (6.9%). The most common pain characteristics were a squeezing sensation (48.3%) and throbbing (41.4%), while cramping (6.9%) and a pulling sensation (3.4%) were reported by a small number of respondents. Almost all respondents experienced intermittent pain (86.2%), whereas 13.8% experienced continuous pain. The pain most frequently began on the first day of menstruation. Conclusion: Dysmenorrhea among IUD users was predominantly mild, characterized by a squeezing sensation and an intermittent pattern. These findings can serve as a basis for healthcare professionals to improve education and counseling regarding the side effects of IUD use. Suggestions: IUD users are encouraged to increase their knowledge regarding the side effects of IUD use. Future research should consider using larger sample sizes and investigating other factors that may influence the incidence of dysmenorrhea among IUD users such as the type of IUD, physical activity, psychological factors, history of dysmenorrhea, and duration of IUD use to obtain more in-depth results.